Synthesis and biological evaluation of ursolic acid derivatives bearing triazole moieties as potential anti-Toxoplasma gondii agents - Tian Luan; Chunmei Jin; Chun-Mei Jin; Guo-Hua Gong; Zhe-Shan Quan (Taylor & Francis Group, 2019)
Ursolic acid (UA), a plant-derived compound, has many properties beneficial to health. In the present study, we synthesised three series of novel UA derivatives and evaluated their anti-Toxoplasma gondii activity both in vitro and in vivo. Most derivatives exhibited an improved anti-T. gondii activity in vitro when compared with UA (parent compound), whereas compound 3d exhibited the most potent anti-T. gondii activity in vivo. Spiramycin served as the positive control. Additionally, determination of biochemical parameters, including the liver and spleen indexes, indicated compound 3d to effectively reduce hepatotoxicity and significantly enhance anti-oxidative effects, as compared with UA. Furthermore, our molecular docking study indicated compound 3d to possess a strong binding affinity for T. gondii calcium-dependent protein kinase 1 (TgCDPK1). Based on these findings, we conclude that compound 3d, a derivative of UA, could act as a potential inhibitor of TgCDPK1.